Effect of an Active Break Intervention on Attention, Concentration, Academic Performance, and Self-Concept in Compulsory Secondary Education - Espoz-Lazo, S (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
(1) Background: Society’s shift to a tech-focused era and has created a hyper-connected, sedentary lifestyle. The purpose of this study is to address two objectives: firstly, to describe and analyze the effects of an active breaks program associated with the learning of curricular content (CF-AB) on levels of attention, concentration, and academic performance (AP); secondly, to examine the relationship between intense physical activity (PA), attention, concentration, academic self-concept, basic psychological needs, and academic performance in schoolchildren who practice CF-ABs. (2) Method: A randomized controlled trial quasi-experimental pre-test/post-test study with a non-probabilistic sample included 313 secondary school students divided into intervention and control groups. The intervention, a curricular-focused academic break (CF-AB) (8 weeks, 5–10 min/session), is taken in the middle of the class and linked with the subject content. Measuring instruments: Attention Test D2, ad hoc test for the AP, self-concept AF5, Basic Psychological Needs Satisfaction Scale in General (BNSG-S), and the Global PA Questionnaire (GPAC.V2). (3) Results: Attention and concentration improved in both groups, with no significant differences. There were no significant differences in academic self-concept, but the intervention group showed higher scores in basic psychological needs. AP correlated positively with concentration, academic self-concept, and physical activity. A proportion of 20% of the variance of AP in spelling is explained by the regression model. Students who improved the most in AP practiced intense PA outside school, with good self-concept and satisfactory social relationships. Although concentration was related to AP, it did not explain the improvement. (4) Conclusion: CF-ABs may have a positive impact on attention and AP, with socioemotional factors and PA playing an important role in this effect. (5) Limitations and Future Research: The relationship between PA performed in class and AP should be considered with caution due to the multifactorial nature of AP. Future research should consider the number of sessions per week, the prolongation of the same during the school year, the intensity and duration of the activity, and the intervention type of active breaks. In addition, attention should be paid to possible incident factors in AP related to personal and social variables. © 2024 by the authors.